Evaluación de nosodes homeopáticos en el tratamiento de mastitis subclínica bovina y calidad de leche en el cantón Mejía hacienda Puichig, Pichincha, 2015 - Aymara Quinga, Jaime Enrique (2015)
He present investigation was developed in the Treasury Puichig, belonging to the canton Mejía, in the one which the effect of homeopathic nosodes was evaluated about the quality of the milk, in affected animals of mastitis bovine subclinic, to which are diagnosed by means of the test CMT, the samples of milk were analyzed in a laboratory veterinary physical, chemical as well as bacteriological parameters, to the beginning and the end of our investigation. For this investigation 18 were used bovine of Race Holstein Friesian Mestizos, which were divided in 3 treatments where the (Treatment 1) it corresponded to the application Anus-flow, the (Treatment 2) to the Sub-lingual application and the (Treatment 3) to the application intramamaria of a pharmacological....